Evidence for 2.35 to 2.30 Ga juvenile crustal growth in the northwest Borborema Province, NE Brazil - Dos Santos, Ticiano J.S.; Fetter, Allen H.; Van Schmus, W. Randall; Hackspacher, Peter C. [UNESP] (Geological Society of London, 2009)
The c. 600 Ma Brasiliano Borborema Province of NE Brazil comprises a complex collage of Precambrian crustal blocks cut by a series of continental-scale shear zones. The predominant basement rocks in the province are 2.1-2.0 Ga Transamazonian gneisses of both juvenile and reworked nature. U-Pb zircon and Sm-Nd whole-rock studies of tonalite-trondhjemite-granodiorite basement gneisses in the NW Ceará or Médio Coreaú domain in the northwestern part of the Borborema Province indicate that this represents a continental fragment formed by 2.35-2.30 Ga juvenile crust. This block has no apparent genetic affinity with any other basement gneisses in the Borborema Province, and it does not represent the tectonized margin of the c. 2.1-2.0 Ga São Luis Craton to the NW. The petrological and geochemical characteristics, as well as the Nd-isotopic signatures of these gneisses, are consistent with their genesis in an island arc setting. This finding documents a period of crustal growth during a period of the Earth's history which is known for its tectonic quiescence and paucity of crust formation. © Geological Society of London 2009.
Keywords: basement rock; continental margin; crustal evolution; geochemistry; gneiss; granodiorite; island arc; petrology; Precambrian; samarium-neodymium dating; shear zone; tectonic evolution; tectonic setting; tonalite; trondhjemite; uranium-lead dating; Borborema; Brazil